Measure of Tourism Productivity and its Relationship with Domestic Tourism Product in Mexico - Jazmín Lubina Avalos Arias; Santiago Marquina Benítez; Antonio Kido Cruz; Ma. Teresa Kido Cruz (European Scientific Journal, ESJ, 2019)
In this paper, the main object of the study is to obtain a measure of tourism productivity and a measure of the level and type of relationship between the value of production of tourism and tourism productivity of Mexico tourism for the period 2008-2013. The Methodological framework was the input-output matrices, to correlate standardized values of the production value with tourism productivity for the 30 “tourism” subsectors. Considering that the explanation for the economic growth is very different and complex in all the countries, but the correlation study only manages that is possible to identify the variations of the tourism productivity, and that they are associated directly to the value of tourism production. The results show that the sectors with negative productivity are other hosting services, foreign buses, pharmaceuticals, films, photography, movies and car rentals, and positive productivity sectors are: handicrafts, hotels, food, beverages, restaurants and bars, trade and other financial and insurance services. Also, a direct relationship between production and productivity was found.